Protein Expression Analysis by Western Blot and Protein–Protein Interactions - Cima-Cabal, María Dolores; Vázquez, Fernando; de los Toyos, Juan R; García-Suárez, María del Mar (Methods in Molecular Biology, 2020)
Western blot analysis is widely used for detecting protein expression, analysis of protein–protein interactions, and searching for new biomarkers. Also, it is a diagnostic tool used for detection of human diseases and microorganism infections. Some Streptococcus pneumoniae proteins are important virulence factors and a few of them are diagnostic markers. Here, we describe the detection of two pneumococcal proteins, pneumolysin and PpmA, in human urine by using monoclonal and polyclonal antibodies.
Capítulo del libro "Iovino F. (eds) Streptococcus pneumoniae. Methods in Molecular Biology, vol 1968. Humana Press, New York, NY"
Keywords: monoclonal antibody; pneumolysin; PpmA; urine; western-blot; Scopus(2); WOS(2)